PENINGKATAN PEMAHAMAN ILMU SHOROF MELALUI METODE DRILL PADA PEMBELAJARAN PAI - Moch Rizky Fajar Alamsyah (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study departs from the low understanding of 9th-grade students regarding shorof (Arabic morphology) at Daarul Ihsan School Bandung. Shorof, which studies word form changes (tashrif), is a critical foundation for comprehending Islamic religious texts. This Classroom Action Research (CAR) examined the effectiveness of the Drill Method in improving shorof comprehension among 32 students over two cycles. Data were collected through written tests, observation, and documentation. Results demonstrated significant improvement: the class average in the pre-cycle was 62.5 with a passing rate of 37.5%, rising to 73.4 (65.6% passing) in Cycle I, and reaching 84.2 (93.75% passing) in Cycle II. These findings confirm that the Drill Method, through systematic and structured repetitive practice, effectively strengthens memory retention, develops morphological reflexes, and builds student confidence in independently applying tashrif rules.